2015
DOI: 10.2903/j.efsa.2015.4289
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re‐evaluation of ascorbyl palmitate (E 304(i)) and ascorbyl stearate (E 304(ii)) as food additives

Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion reevaluating the safety of ascorbyl palmitate (E 304(i)) and ascorbyl stearate (E 304(ii)) as food additives. The use of these food additives was evaluated by the Joint FAO/WHO Expert Committee on Food Additives and by the Scientific Committee on Food. Biological data on ascorbyl palmitate and stearate are sparse and the safety assessment of them for use as food additives is mainly based on the assumption that asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This could be associated with the initial acidity of HPBF or the stability and structure of L-AP. Under acidic conditions, L-AP could be entirely hydrolyzed to ascorbic acid and their respective fatty acids in the reporter of EFSA and ANS ( 43 ), which affect its own free radical scavenging ability. Comparatively, TBHQ had a noticeable effect on scavenging free radicals terminating the free radical chain reaction, which could be attributed to its molecular structure, high thermal resistance and stability.…”
Section: Resultsmentioning
confidence: 99%
“…This could be associated with the initial acidity of HPBF or the stability and structure of L-AP. Under acidic conditions, L-AP could be entirely hydrolyzed to ascorbic acid and their respective fatty acids in the reporter of EFSA and ANS ( 43 ), which affect its own free radical scavenging ability. Comparatively, TBHQ had a noticeable effect on scavenging free radicals terminating the free radical chain reaction, which could be attributed to its molecular structure, high thermal resistance and stability.…”
Section: Resultsmentioning
confidence: 99%
“…E304i, ascorbyl palmitate, is generally recognized as safe (GRAS) and approved by the US Food and Drug Administration (USFDA) as a food additive. It is frequently used as an antioxidant or as a fat-soluble form of vitamin C. The European Food Safety Authority (EFSA) is in line with the American authorities and has also concluded that there is no safety concern regarding using E304i as a food additive ( 15 ). According to EFSA, E304i is considered to have the same biological effects as ascorbic acid, and from human data, it was concluded that supplementary doses of approximately 1 g/person per day in addition to normal dietary intake are not associated with adverse gastrointestinal effects, but gastrointestinal acute effects may occur at doses exceeding 3–4 g/day.…”
Section: Methodsmentioning
confidence: 98%
“…However, its application as a substitute for nitrites in foods is very limited due to its pro-oxidant behavior . Calcium ascorbate (E302) is used in dairy products, cured or cooked meat products, to dip freshly cut fruit and prevent browning, to intensify the color of cured meat, and to act as a synergist for other antioxidants. , Fatty acid esters of ascorbic acid (E304) can be used in dairy products, chewing gums, cereals, meats, desserts, salads, sauces, and others . Erythorbates (E315–E316) are mostly dissipated in cured meats, frozen fruits, vegetables, oils, fats, seafood, and fish with the function of reducing the formation of nitrosamines during curing or cooking .…”
Section: Food Preservativesmentioning
confidence: 99%
“… 138 , 139 Fatty acid esters of ascorbic acid (E304) can be used in dairy products, chewing gums, cereals, meats, desserts, salads, sauces, and others. 140 Erythorbates (E315–E316) are mostly dissipated in cured meats, frozen fruits, vegetables, oils, fats, seafood, and fish with the function of reducing the formation of nitrosamines during curing or cooking. 141 Sodium lactate (E325) and potassium lactate (E326) are used as antimicrobials in processed and unprocessed meats, sausages, meat burgers, and fish.…”
Section: Food Preservativesmentioning
confidence: 99%